Pandemic Protagonists Viral (Re)Actions in Pandemic and Corona Fictions - Völkl, Yvonne; Obermayr, Julia; Hobisch, Elisabeth (Edition Kulturwissenschaft, 2023)
During the first mandatory lockdowns of the Covid-19 pandemic, citizens worldwide turned to »pandemic fictions« or started to produce their own »Corona Fictions« across different media. These accounts of (previously) experienced or imagined health crises feature a great variety of protagonists and their (re)actions in response to the exceptional circumstances. The contributors to this volume take a closer look at different pandemic protagonists in fictional narratives relating to the Covid-19 pandemic as well as in existing pandemic fictions. Thereby they provide new insights into pandemic narratives from a cultural, literary, and media studies perspective from antiquity to today.